Trial watch: Peptide-based vaccines in anticancer therapy. (2nd December 2018) - Bezu, Lucillia; Kepp, Oliver; Cerrato, Giulia; Pol, Jonathan; Fucikova, Jitka; Spisek, Radek; Zitvogel, Laurence; Kroemer, Guido; Galluzzi, Lorenzo
ABSTRACT: Peptide-based anticancer vaccination aims at stimulating an immune response against one or multiple tumor-associated antigens (TAAs) following immunization with purified, recombinant or synthetically engineered epitopes. Despite high expectations, the peptide-based vaccines that have been explored in the clinic so far had limited therapeutic activity, largely due to cancer cell-intrinsic alterations that minimize antigenicity and/or changes in the tumor microenvironment that foster immunosuppression. Several strategies have been developed to overcome such limitations, including the use of immunostimulatory adjuvants, the co-treatment with cytotoxic anticancer therapies that enable the coordinated release of damage-associated molecular patterns, and the concomitant blockade of immune checkpoints. Personalized peptide-based vaccines are also being explored for therapeutic activity in the clinic. Here, we review recent preclinical and clinical progress in the use of peptide-based vaccines as anticancer therapeutics.Abbreviations: CMP: carbohydrate-mimetic peptide; CMV: cytomegalovirus; DC: dendritic cell; FDA: Food and Drug Administration; HPV: human papillomavirus; MDS: myelodysplastic syndrome; MHP: melanoma helper vaccine; NSCLC: non-small cell lung carcinoma; ODD: orphan drug designation; PPV: personalized peptide vaccination; SLP: synthetic long peptide; TAA: tumor-associated antigen; TNA: tumor neoantigen